Pelatihan Bahasa Inggris Dasar Bagi Anak Usia Dini Di Pesisir Pantai Ampenan - NTB - Etika Ariyani (Yayasan Kajian Riset dan Pengembangan RADISI, 2021)
basic english training for early childhood which lived at ampenan coastline, Lombok - West Nusa Tenggara Province aims to introduced basic English for early childhood so it can be the best investment for their future. this training program held for seven weeks, 60 minutes for a meeting. the training materials consists of language functions and vocabulary by using songs and games which can arouse the participants motivation to learn English. the result of this training program shown that there is an improvement of the participants skills significantly at their communication ability. they motivated to used english in their daily interaction because created interesting teaching learning process.